A call for discovery: Re‐envisioning The Cancer Genome Atlas as a blueprint for a TCGA2.0—The COVID‐19 Genome Atlas. Issue 1 (18th October 2021) - Hargadon, Kristian M.
Abstract: The COVID‐19 pandemic has impacted the health of millions and had a myriad of devastating consequences for global societies since its emergence in 2019. Noting parallels between the impact of COVID‐19 and cancer as diseases of global health significance, and as a way of building off the successes of The Cancer Genome Atlas (TCGA) as a comprehensive, multiomics approach to understand and combat cancer, this Call For Discovery provides a vision for creating a new TCGA2.0 (The COVID‐19 Genome Atlas) as a tool that will benefit researchers, clinicians, and patients alike as the scientific community works to better understand not only the various determinants of COVID‐19 disease outcome but also the most effective ways to manage and treat COVID‐19 disease complications.